Analysis of Twenty-third Amendment of Constitution of Islamic Republic of Pakistan: Impacts and Prospects - Khan, Muhammad Mumtaz Ali; Hassan, Abida; Rao, Sadia Saeed (Annals of Human and Social Sciences, 2024)
This research highlights the importance of constitutional amendments and specifically those which were exercised after 18th amendment, when the provinces were given autonomy to regulate their administrative and all other matters with full liberty. Later on also many amendments were adopted by the Constitution of Pakistan, 1973. The most important is 23rd amendment which was passed on 30th of March 2017 which caused a significant change in the history of judicial process. Under this amendment, Military Courts were established which were also established prior to this amendment and those were subject to the amendment of 21st amendment in the Constitution od Pakistan, 1973. This article highlights the pros and cons of establishment of Military Courts and its effects on judicial system of Pakistan as well as on civilians of Pakistan. It is purely qualitative study and based on primary as well as secondary sources. At the end of the article. It has been concluded with precise suggestions.